2017
DOI: 10.4178/epih.e2017022
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors among nurses in teaching hospitals in the west of Iran: what we need to know about prevalence, types, and barriers to reporting

Abstract: OBJECTIVES This study aimed to examine the prevalence and types of medication errors (MEs), as well as barriers to reporting MEs, among nurses working in 7 teaching hospitals affiliated with Kermanshah University of Medical Sciences in 2016. METHODS A convenience sampling method was used to select the study participants (n=500 nurses). A self-constructed questionnaire was employed to collect information on participants’ socio-demographic characteristics (10 items), thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
81
7
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 23 publications
8
81
7
10
Order By: Relevance
“…This study explored nursing students’ opportunity to report and discuss PS issues and associated factors during their most recent clinical training. Although incident reporting has been considered essential in improving patient safety, a consistent proportion of errors, near misses or PS issues is not usually reported by students and health care practitioners …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study explored nursing students’ opportunity to report and discuss PS issues and associated factors during their most recent clinical training. Although incident reporting has been considered essential in improving patient safety, a consistent proportion of errors, near misses or PS issues is not usually reported by students and health care practitioners …”
Section: Discussionmentioning
confidence: 99%
“…In conditions of understaffing or poor quality of care, students are more likely to be left alone in tackling PS issues, without discussing safety issues and receiving constructive feedback from their instructors . In addition, overworked nurses fail to report errors and have an increased likelihood of making mistakes because of the higher workloads . Therefore, students may be exposed to negative role modelling that may facilitate the learning of unsafe professional behaviours, which lead to different interventions being prioritised rather than protection of patient safety …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the medications are administered by nurses [7]. The frequently perpetrated types of MAEs include wrong dose, wrong time, wrong drug, wrong route, omission of doses, wrong patient, lack of documentation, and technical errors [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite extensive efforts directed towards ensuring patient safety, numerous nurses still commit undesired errors. For example, an Iranian study reported a 17% prevalence of medication errors among nurses, the most usual of which are inaccurate medication timing (24.0%) or dosage (16.8%) and administration to a different patient (13.8%; Fathi et al, 2017). A systematic review revealed that nurse staffing was related to increased healthcare‐associated infection incidences (Mitchell, Gardner, Stone, Hall, & Pogorzelska‐Maziar, 2018).…”
Section: Introductionmentioning
confidence: 99%